Peningkatan Aktivitas dan Hasil Belajar Siswa pada Pembelajaran IPA Materi Gerak Benda Melalui Pendekatan Saintifik - SETYAWAN, CHRISNA (Trapsila: Jurnal Pendidikan Dasar, 2019)
There are four aspects of skills in Indonesian language learning that must be mastered by students, namely listening, speaking, reading and writing skills. But in reality, when Indonesian language learning takes place, most students are less skilled in writing skills. Based on preliminary observations in teaching and learning activities Indonesian language is less interesting and students' interest in learning, especially in writing learning. The purpose of this study is to improve short essay writing skills in class II SDN RW X Demak Jaya Surabaya through the use of serial image media. This type of research is Classroom Action Research (CAR). The subject of this study was the second grade students of SDN RW X Demak Jaya Surabaya in the 2017-2018 school year with 37 students. One class consists of 18 male students and 19 female students. This research was conducted in two cycles. The results showed that the use of serial image media can improve short essay writing skills. This can be evidenced by the acquisition of student activity values that have increased from the first cycle of 52.5% to 77.5% in cycle II. While the teacher's activity scored 50% in the first cycle and increased to 77.5% in the second cycle. The percentage of completeness of students also increased, namely in the first cycle 59,45% to 86,48% in the second cycle.